ACCEPTABILITY OF CHEESE STICK WITH ADDITION OF WET ANCHOVY FLOUR (Stolephorus sp.) TO PRE-SCHOOL CHILDREN - Risnawati Assa; Hendrayati Hendrayati; Lydia Fanny (Media Gizi Pangan, 2018)
The utilization of marine fisheries resources gives an important contribution to the economy and health. However, this utilization does not work well due to the complexity of the problems faced regarding technical, social, economic and environmental factors. The one effort to use itis by utilizing anchovy into wet anchovy flour (Stolephorus sp.) in the form of cheese stick snacks that contain enough protein and rich of calcium. This study aims to determine the acceptability of cheese stick with the addition of wet anchovy flour (Stolephorus sp.). This type of research is the pre-experimental with post test group design. The acceptance was assessed based on a hedonic test of 30 panelists. The results of the best acceptance powerare done by food weighing method for intake levels in pre-school children then presented in the form of tables and narratives. The results shows that the highest acceptability of panelists is against the cheese stick with the addition of 10% wet anchovy flour (Stolephorus sp.). The fact also reveals that as many as 80% of the panelists liked the flavor aspect, 70% of the panelists liked the color aspect, 73.33% of the panelists liked the aroma aspect, and 90% of the panelists liked the texture aspect. The results of research on consumer panelists convey that the acceptability of pre-school children with good categories is 53.33%. Therefore, it is recommended in making cheese stick with the addition of wet anchovy flour (Stolephorus sp.) is to use a concentration of 10% because it is preferred from the aspect of color, texture, aroma and taste, and compared with the standard or concentration of 0%.